Bio-Mimetic Vision System For Autonomous Mobile Robot Navigation - Muhammad Safwan; Muhammad Yasir Zaheen; M. Anwar Ahmed; Muhammad Shujaat Kamal; Raj Kumar (Sir Syed University Research Journal of Engineering and Technology)
Bio-Mimetic Vision System (BMVS) for Autonomous Mobile Robot Navigation encompasses three major fields, namely robotics, navigation and obstacle avoidance. Bio-mimetic vision is based on stereo vision. Summation of Absolute Difference (SAD) is applied on the images from the two cameras and disparity map is generated which is then used to navigate and avoid obstacles. Camera calibration and SAD is applied on Matlab software. AT89C52 microcontroller, along with Matlab, is used to efficiently control the DC motors mounted on the robot frame. It is observed from experimental results that the developed system effectively distinguishes objects at different distances and avoids them when the path is blocked.